2019
DOI: 10.1007/s11027-019-09879-0
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a 100-MW solar-powered thermo-chemical air separation system combined with an oxy-fuel power plant for bio-energy with carbon capture and storage (BECCS)

Abstract: The combination of concentrated solar power-chemical looping air separation (CSP-CLAS) with an oxy-fuel combustion process for carbon dioxide (CO 2 ) capture is a novel system to generate electricity from solar power and biomass while being able to store solar power efficiently. In this study, the computer program Advanced System for Process Engineering Plus (ASPEN Plus) was used to develop models to assess the process performance of such a process with manganese (Mn)-based oxygen carriers on alumina (Al 2 O 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…To be included, supply chains must: utilize a UK domestic feedstock; the biomass types must cover a range of spatial distributions; similar supply chains should be mentioned in industrial and governmental reports; must use a mixture of carbon capture technologies; must cover a range of different types of BECCS; and one must generate hydrogen fuel. Based on a literature search, the following three supply chains met all of the criteria and have been used in this analysis (Muresan et al, 2013;Moreira et al, 2016;Mendiara et al, 2018;Pour et al, 2018;Tagomori et al, 2019;Agrawal and Rao, 2020;Emenike et al, 2020;Ghiat et al, 2020;Patzschke et al, 2020;García-Freites et al, 2021):…”
Section: Methodology Beccs Supply Chain Descriptionsmentioning
confidence: 99%
“…To be included, supply chains must: utilize a UK domestic feedstock; the biomass types must cover a range of spatial distributions; similar supply chains should be mentioned in industrial and governmental reports; must use a mixture of carbon capture technologies; must cover a range of different types of BECCS; and one must generate hydrogen fuel. Based on a literature search, the following three supply chains met all of the criteria and have been used in this analysis (Muresan et al, 2013;Moreira et al, 2016;Mendiara et al, 2018;Pour et al, 2018;Tagomori et al, 2019;Agrawal and Rao, 2020;Emenike et al, 2020;Ghiat et al, 2020;Patzschke et al, 2020;García-Freites et al, 2021):…”
Section: Methodology Beccs Supply Chain Descriptionsmentioning
confidence: 99%
“…The OCM reactor feeds CH 4 and a combination of O 2 and vapor phase moist H 2 O 2 . The O 2 is produced in a solar powered air separation plant [23] that enjoys the energy and economic savings from chemical looping instead of cryogenic separation [24,25]. Aqueous H 2 O 2 is produced by the solar powered catalyzed reaction of O 2 and acidic liquid H 2 O [20].…”
Section: Simple Layout Of a "Green" Ocm Plantmentioning
confidence: 99%
“…Recent research shows that an enormous amount of AWB is produced annually worldwide (~4 billion tonnes/year), representing a favourable outlook in terms of utilization and valorization ( Patzschke et al, 2020 ). Hamelin et al (2019) quantified the waste biomass potential in the EU-27 and found that 13 European countries have the highest amount of waste available (above 20 PJ y −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The action plan of the bioeconomy strategy 'Innovating for Sustainable Growth' issued by the EU in 2012 prioritized investment in research and innovation over specific actions to improve knowledge on the availability and potential of AWB for manufacturing high-value-added products (European Commission, 2012). The new bioeconomy strategy 'strengthen ing the connection between economy, society and the environ ment' (2018) also prioritizes Research and Innovation for the deployment of innovative solutions for the production of new and sustainable bio-based products (European Commission, 2018) Recent research shows that an enormous amount of AWB is produced annually worldwide (~4 billion tonnes/year), representing a favourable outlook in terms of utilization and valorization (Patzschke et al, 2020). Hamelin et al (2019) quantified the waste biomass potential in the EU-27 and found that 13 European countries have the highest amount of waste available (above 20 PJ y −1 ).…”
Section: Introductionmentioning
confidence: 99%